An unbiased, sustainable, evidence-informed Universal Food Guide: a timely template for national food guides - Elizabeth Dean; Jia Xu; Alice Yee-Men Jones; Mantana Vongsirinavarat; Constantina Lomi; Pintu Kumar; Etienne Ngeh; Maximilian A. Storz (Nutrition Journal)
Abstract Background Although national food guides are designed, ostensibly, to translate scientific evidence with respect to food, dietary patterns, and health, their development has increasingly become a corporate/political process as well as scientific one; often with corporate/political influences overriding science. Our aim was to construct an unbiased, sustainable, evidence-informed Universal Food Guide to serve as a template for countries to develop their unique guides, thereby, provide a valid resource for health professionals, health authorities, and the public. Methods To address our aim, we conducted an integrative review of multiple evidence-informed sources (e.g., established databases, evidence syntheses, scholarly treatises, and policy documents) related to four areas: 1. Food guides’ utility and conflicts of interest; 2. The evidence-based healthiest diet; 3. Constituents of the Universal Food Guide template; and 4. Implications for population health; regulation/governance; environment/climate/planetary health; and ethics. Results The eating pattern that is healthiest for humans (i.e., most natural, and associated with maximal health across the life cycle; reduced non-communicable disease (NCD) risk; and minimal end-of-life illness) is whole food, low fat, plant-based, especially vegan, with the absence of ultra-processed food. Disparities in national food guide recommendations can be explained by factors other than science, specifically, corporate/political interests reflected in heavily government-subsidized, animal-sourced products; and trends toward dominance of daily consumption of processed/ultra-processed foods. Both trends have well-documented adverse consequences, i.e., NCDs and endangered environmental/planetary health. Commitment to an evidence-informed plant-based eating pattern, particularly vegan, will reduce risks/manifestations of NCDs; inform healthy food and nutrition policy regulation/governance; support sustainable environment/climate and planetary health; and is ethical with respect to ‘best’ evidence-based practice, and human and animal welfare. Conclusion The Universal Food Guide that serves as a template for national food guides is both urgent and timely given the well-documented health-harming influences that corporate stakeholders/politicians and advisory committees with conflicts of interest, exert on national food guides. Such influence contributes to the largely-preventable NCDs and environmental issues. Policy makers, health professionals, and the public need unbiased, scientific evidence as informed by the Universal Food Guide, to inform their recommendations and choices.